West Virginia Regulatory Program (The Federal Register / FIND, 2009)
Proposed rule; public comment period and opportunity for public hearing on proposed amendment. CFR Part: "30 CFR Part 948" Citation: "74 FR 53972" Document Number: "WV-116-FOR; OSM-2009-0008" Page Number: "53972" "Proposed Rules" SUMMARY: We are announcing receipt of a proposed amendment to the West Virginia regulatory program (the West Virginia program) under the Surface Mining Control and Reclamation Act of 1977 (SMCRA or the Act) that includes both statutory and regulatory revisions. West Virginia submitted a proposed amendment authorized by Committee Substitute for Senate Bill 153 to revise the West Virginia Code of State Regulations (CSR) concerning the continued oversight by the Secretary of "approved persons" who prepare, sign, or certify mining permit applications and related materials; regarding incidental boundary revisions (IBR) to existing permits, by clarifying that certain types of collateral activities are part of the primary mining operations and therefore subject to the same acreage limitations, while providing more relevant and exacting criteria for the Secretary to consider in evaluating an application for revision; deleting the bonding matrix forms; changing term "Bio-oil" to "Bio fuel"; and clarifying standards in subsection 9.3.f that pertain to areas developed for hayland or pasture use. West Virginia submitted proposed changes as contained in Senate Bill 436 which amends WV Code 22-3-8 by changing references regarding "the commissioner of the Bureau of Employment Programs" and "the executive director of the workers' compensation commissioner" which are considered non-substantive.